Prediction of Survival in Infants with Congenital Diaphragmatic Hernia Based on Stomach Position, Surgical Timing, and Oxygenation Index - Mann, Paul C.; Morriss, Frank H., Jr.; Klein, Jonathan M. (American Journal of Perinatology, 2012)
Objective To identify characteristics predictive of survival of patients with congenital diaphragmatic hernia (CDH).Study Design Retrospective analysis of clinical characteristics including severity of lung disease measured by oxygenation index (OI) associated with single-center survival in CDH patients (n = 81) from 1992 to 2008. Data were analyzed using univariate and multivariable logistic regression, effect plots, and receiver operating characteristic (ROC) plots.Results No patient died if the stomach was located in the abdomen. A left thoracic stomach position predicted decreased survival with ROC area under the curve (AUC) = 0.70. OI of ≤26 averaged over the first 12 hours of life predicted ≥50% survival for all patients, with AUC = 0.86. OI effect plots allow prediction of survival over a continuous OI range. No patient survived if mean OI was >51 in the first 12 hours of life. Delaying surgery for a median of 6 days improved survival probability for all patients with presurgery OI values ≤51.Conclusion Position of the stomach in the abdomen, delayed surgery, and less severe cardiopulmonary disease during the first 12 hours of life, as measured by mean OI, predicted improved survival probability among patients with CDH. Our CDH model, using mean OI, permits specific individual prediction of survival probability over a range of OI values.
Keywords: predictive rule; congenital diaphragmatic hernia; oxygenation index; survival modeling; surgical timing